A Clarion Call for Social Work Attention: Brothers and Sisters of Persons With Acquired Brain Injury in the United States. Issue 3 (12th December 2016) - Degeneffe, Charles Edmund
ABSTRACT: This article presents a clarion call for increased social work attention to the needs of siblings of persons with acquired brain injury (ABI) in the United States. The article overviews how siblings are psychosocially affected, how they provide care to the injured brothers and sisters, and how they personally develop as a result of their experiences. The article highlights the fact that social workers and other professionals often overlook the needs of siblings of persons with ABI and makes an appeal for social workers to advance clinical practice and research to benefit this often neglected population.